2005
DOI: 10.1083/jcb.200501093
|View full text |Cite
|
Sign up to set email alerts
|

SNAREs can promote complete fusion and hemifusion as alternative outcomes

Abstract: Using a cell fusion assay, we show here that in addition to complete fusion SNAREs also promote hemifusion as an alternative outcome. Approximately 65% of events resulted in full fusion, and the remaining 35% in hemifusion; of those, approximately two thirds were permanent and approximately one third were reversible. We predict that this relatively close balance among outcomes could be tipped by binding of regulatory proteins to the SNAREs, allowing for dynamic physiological regulation between full fusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 54 publications
11
124
0
Order By: Relevance
“…A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8). These results suggest that the SNARE-dependent fusion of intracellular membranes like yeast vacuoles might also proceed through a hemifusion intermediate.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A hemifusion intermediate was also detected at the single-liposome level by monitoring FRET between membrane-bound fluorophores in single fusion events between pairs of SNARE-reconstituted liposomes (7), and in flipped SNARE-mediated cell-cell fusion (8). These results suggest that the SNARE-dependent fusion of intracellular membranes like yeast vacuoles might also proceed through a hemifusion intermediate.…”
Section: Discussionmentioning
confidence: 70%
“…Hemifusion has been directly observed with influenza HA (3)(4)(5), either wild-type or with a GPI-anchor in place of its transmembrane domain (TMD), in a minimal SNARE-driven liposome fusion system (6, 7) with low levels of wild-type SNARE proteins or with mutant SNARE proteins with partial TMDs that span only one bilayer leaflet (6). Hemifusion was also observed in cell-cell fusion mediated by GPI-anchored SNARE proteins expressed on the outer surface of the plasma membrane (8), suggesting that all SNARE-dependent fusion might proceed by means of hemifusion. A hemifusion intermediate was proposed for yeast vacuole fusion, based on the finding that GTP␥S allows lipid mixing while blocking the fusion-dependent activation of pro-Pho8p (9).…”
mentioning
confidence: 99%
“…To test this, we developed a cell-cell fusion assay to detect lipid mixing (hemifusion) as well as content mixing (full fusion) based on a soluble NSF attachment receptor (SNARE) hemifusion assay reported previously (16). CHO cells lack the lipid ganglioside GM1 (16), so lipid mixing could be detected by using a TRITC-conjugated form of cholera toxin ␤-subunit (CTX) when CHO cells were fused to cells that express GM1.…”
Section: Results Gb Is Not Required For Hemifusionmentioning
confidence: 99%
“…Recent studies have suggested that this process proceeds through a hemifused state in which the outer membrane leaflets fuse first, followed by fusion of the inner membrane leaflets (10)(11)(12)(13). Formation of the hemifused state is characterized by significant physical constraints, because the outer leaflet needs to bend in a tight negative curve to preserve membrane integrity.…”
Section: Snap23 ͉ Syntaxin 4 ͉ Vamp2mentioning
confidence: 99%
“…It has been recently reported that SNARE-mediated membrane fusion occurs through a hemifusion intermediate state (10)(11)(12)(13). Therefore, we next determined the effect of different phospholipid compositions on the proportion of hemifused versus fused membrane states.…”
Section: The Hemifusion Step Is the Rate-limiting Factor For In Vitromentioning
confidence: 99%